2016
DOI: 10.1002/hed.24516
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of smoking on prognosis in human papillomavirus–associated oropharyngeal carcinoma

Abstract: Smoking was the only modifiable prognostic factor in HPV-positive patients. Therefore, active stop-smoking programs must be integrated in the routine management of patients to maximize treatment results. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1780-1787, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…Several studies have found smoking to be significantly associated with worse prognosis among HPV‐positive OPSCC patients, but this association was not detected in our HPV‐positive patients. This may be due to the retrospective nature of this study, as medical records may not have fully captured tobacco exposure.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Several studies have found smoking to be significantly associated with worse prognosis among HPV‐positive OPSCC patients, but this association was not detected in our HPV‐positive patients. This may be due to the retrospective nature of this study, as medical records may not have fully captured tobacco exposure.…”
Section: Discussioncontrasting
confidence: 84%
“…Few studies have focused on prognostic factors for survival after stratification for HPV status in OPSCCs. Initial studies suggest that among patients with HPV‐positive OPSCCs, older age, smoking, and higher American Joint Committee on Cancer (AJCC) 7th edition tumor stage are associated with worse locoregional control and overall survival . Race has been observed as a prognostic factor for HPV‐negative OPSCC, but not HPV‐positive OPSCC .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with HPV‐related OPC, who likely comprised the majority of the analytic population in the current study, are known to have lower rates of tobacco abuse compared with patients with traditional tobacco‐related HNC. However, the risk of OPC is highest in current and former smokers, and the results of the current study have demonstrated that nearly one‐half of survivors are diagnosed with tobacco abuse by year 5, which is known to increase the risk of CVD, stroke, COPD, tumor recurrence, and the development of new malignancies …”
Section: Discussionmentioning
confidence: 65%
“…However, the risk of OPC is highest in current and former smokers, and the results of the current study have demonstrated that nearly one-half of survivors are diagnosed with tobacco abuse by year 5, which is known to increase the risk of CVD, stroke, COPD, tumor recurrence, and the development of new malignancies. 9,[45][46][47][48][49] In addition, survivors are at moderately high risk of developing depression, anxiety, and alcohol abuse. Data have shown that the risk of suicide among survivors of HNC is nearly twice that of other cancer survivors, and that rate has increased since 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Although smoking has been proven to be a major prognostic factor for HNSCC, there are conflicting results with respect to the role of HPV status and smoking in survival . HPV16 positivity appears to have a greater effect on the prognosis of LSCC in never smokers than ever smokers . In our study, we compared survival outcomes of HPV16 DNA and/or p16 expression stratified by smoking status.…”
Section: Discussionmentioning
confidence: 83%